Optimalisasi Peningkatan Pengetahuan Ibu Tentang Pola Makan Sebagai Upaya Pencegahan Terjadinya Kegawatdaruratan Gizi Buruk dan Gizi Kurang pada Anak - Isra Nur Utari Syachnara Potabuga (Lembaga Pengembangan Kinerja Dosen, 2022)
Malnutrition is currently a global problem in the world, including in Indonesia. Malnutrition is a nutritional status based on a weight-for-age index (BB/U) < -3 SD which is the equivalent of a very underweight body weight. One of the problems of malnutrition that is still quite high in Indonesia, especially the problem of stunting and wasting in toddlers. Toddlers are an age group that is vulnerable to nutritional disorders because at this time they need optimal nutrition for their growth and development. According to the World Health Organization (WHO) malnutrition causes 54% of infant and child deaths. The incidence of malnutrition in Indonesia among toddlers in 2018 is still high, namely 17.7% compared to the 2019 target of the National Medium Term Development Plan (RPJMN) of 17%. Getting into the habit of eating nutritious and varied foods is the key to preventing malnutrition and malnutrition. This community service is carried out with the aim of Optimizing Increasing Mother's Knowledge About Diet as an Effort to Prevent Emergencies of Malnutrition and Undernutrition in Children. The expected outputs from this activity are health education, an increase in knowledge, products and implementation for mothers to anticipate emergencies of malnutrition and undernutrition in children. Plans for implementation in March 2022 at the Toddler Teratai Posyandu, using the seminar method, and discussion/question and answer. The media used are LCD, ppt, and Leafalet/Flyer.